A Survey on Awareness Regarding Certain Common Craniofacial Deformities and its Treatment Approach Among Gujarat Population - Priyal Sanjay Bhavsar; Ajay Kantilal Kubavat; Khyati Viral Patel; Riddhi Patel; Anuj Patel; Vishwa Sejani (Wolters Kluwer Medknow Publications, 2024)
The leading intent of the present questionnaire is to assess the ratio of the concerned population as well as the treatment approach of craniofacial deformities among Gujarat citizenry. The theme of Google Form was used for 100 partakers to record responses via sending the questionnaire in English and Gujarati languages through WhatsApp and Emails. From the 100 respondents which are from laymen of Gujarat, 62.25% of inhabitants are acquainted with craniofacial syndromes, 15% of residents have craniofacial deformities as their family history, 51.66% of denizens have some idea for the treatment approach of craniofacial malformations. A good number of Gujarat laymen have some clear concept for craniofacial syndromes.